Exploring a Theological Foundation of Human Unity and Wholeness in Dialogue with Neurosciences: Revisiting the Vienne Council and Contemporary Christian Anthropologies - Jiménez-Rodríguez, Luis O. (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
Neurosciences are contributing to changing our understanding of human nature. Activities previously attributed to a spiritual, immaterial soul are now associated with the brain. This article presents a foundation to develop a theological and anthropological non-reductive monism that could integrate neuroscientific facts and contribute to the debates about the relation of body and soul. An analysis of the Council of Vienne’s formula «simul unitas» allows its translation as «united as a complete total reality». This revision and a study of contemporary Christian anthropologies inspire some proposed theological concepts of dynamic, soteriological, relational, Christological, and eschatological unity.